Mutation of adjacent cysteine residues in the NSs protein of Rift Valley fever virus results in loss of virulence in a murine model infection - Paweska, Janusz Tadeusz (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.